2018
DOI: 10.24321/2454.325x.201818
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anthropometric Profile and Eating Behavior of Polycystic Ovarian Syndrome (PCOS) Patients with Healthy Controls

Abstract: Introduction: Polycystic ovarian syndrome affects 4% to 23% women, worldwide. Obesity, insulin resistance and uncontrolled eating are usually reported in PCOS. However, there is paucity of data describing associations between eating disorder and PCOS. Aim: To compare the anthropometric profile and eating behavior polycystic ovarian syndrome cases with those of healthy age-matched women. Method: Eighty-five PCOS cases and 85 controls were selected for the study from Gyne OPD of PGIMER, Chandigarh. Anthropometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Eighty‐five PCOS cases and 85 healthy controls were compared, the pattern of eating outside in PCOS cases was three times higher as compared to control and overall BMI was also higher in PCOS cases. It was also observed that PCOS cases had a habit of uncontrolled eating and they were eating more than their daily requirement of calories which clearly shows that changing eating habits and improving lifestyle could show a positive effect in reducing the symptoms related to PCOS (Kaur et al, 2018). In general, eating a healthy diet and avoiding disturbed meal routine may improve overall health and avoid PCOS.…”
Section: Pcos and Dietary Practicesmentioning
confidence: 99%
“…Eighty‐five PCOS cases and 85 healthy controls were compared, the pattern of eating outside in PCOS cases was three times higher as compared to control and overall BMI was also higher in PCOS cases. It was also observed that PCOS cases had a habit of uncontrolled eating and they were eating more than their daily requirement of calories which clearly shows that changing eating habits and improving lifestyle could show a positive effect in reducing the symptoms related to PCOS (Kaur et al, 2018). In general, eating a healthy diet and avoiding disturbed meal routine may improve overall health and avoid PCOS.…”
Section: Pcos and Dietary Practicesmentioning
confidence: 99%